Buckling prevention strategies in nature as inspiration for improving percutaneous instruments: a review. (18th February 2016) - Sakes, Aimée; Dodou, Dimitra; Breedveld, Paul
Abstract: A typical mechanical failure mode observed in slender percutaneous instruments, such as needles and guidewires, is buckling. Buckling is observed when the axial compressive force that is required to penetrate certain tissue types exceeds the critical load of the instrument and manifests itself by sudden lateral deflection of the instrument. In nature, several organisms are able to penetrate substrates without buckling while using apparatuses with diameters smaller than those of off-the-shelf available percutaneous needles and guidewires. In this study we reviewed the apparatuses and buckling prevention strategies employed by biological organisms to penetrate substrates such as wood and skin. A subdivision is made between buckling prevention strategies that focus on increasing the critical load of the penetration tool and strategies that focus on decreasing the penetration load of the substrate. In total, 28 buckling prevention strategies were identified and categorized. Most organisms appear to be using a combination of buckling prevention strategies simultaneously. Integration and combination of these biological buckling prevention strategies in percutaneous instruments may contribute to increasing the success rate of percutaneous interventions.